Perbandingan Sistem Perubahan Konstitusi di Negara Amerika, Perancis dan Indonesia - Faiqah Nur Azizah (UIN Syarif Hidayatullah Jakarta, 2022)
A country's constitution is its most significant component. Creating a state without a constitution is a non-starter. This is due to the fact that it is the most important law at its level. As a result, understanding how a country's governing structure can be altered is critical. The author examines how the United States, France, and Indonesia have implemented a system of constitutional amendments. While France and Indonesia share a legal system, they have a separate procedure for amending their constitutions. Even though Indonesia and the United States have very different legal systems, they both use the same constitutional amendment process. Since America has the world's oldest constitution, it was chosen as the focus of the author's study. As a result, France was picked since the French Revolution had a significant impact on the legal system of several European countries, including Indonesia.